The adaptive resilience of living cultural heritage in a tourism destination. Issue 7 (2nd July 2020) - Bui, Huong T.; Jones, Thomas E.; Weaver, David B.; Le, Andrew
Abstract: This article analyzed a living cultural heritage destination's adaptive resilience from the perspective of social-ecological systems (SES). The aim was to test the SES framework at Hoi An Ancient Town, a cultural World Heritage Site in central Viet Nam by (1) delineating the adaptive renewal cycle in the historical context of destination development; (2) examining community resilience to spatio-cultural changes induced by mass tourism; and (3) identifying characteristics of tourism systems via the control mechanisms of the panarchy's cross-scale interactions. Findings from Hoi An extend the conventional SES approach by revealing the complex context of social relationships that typify human-related adaptation in cultural living heritage destinations. Contrary to conventional SES theory that depicts cross-scale interactions as one-way mechanisms, we propose a multidimensional model of twin interactions concurrently characterized by contrasting forces of bottom-up "revolt" and top-down "remember" functions. Findings from historical, contemporary and systematic dimensions shed light on incorporating Indigenous knowledge and practices into heritage conservation as a form of community resilience. Our analysis also extends the continuity notion of a living heritage site in developing countries, applying an SES framework to complex political, social, cultural and economic concerns in order to contextualize tourism development in Hoi An.